Hand-assisted Approach as a Model to Teach Complex Laparoscopic Hepatectomies: Preliminary Results. Issue 4 (August 2017) - Makdissi, Fabio F.; Jeismann, Vagner B.; Kruger, Jaime A.P.; Coelho, Fabricio F.; Ribeiro-Junior, Ulysses; Cecconello, Ivan; Herman, Paulo
Abstract : Background: Currently, there are limited and scarce models to teach complex liver resections by laparoscopy. The aim of this study is to present a hand-assisted technique to teach complex laparoscopic hepatectomies for fellows in liver surgery. Materials and Methods: Laparoscopic hand-assisted approach for resections of liver lesions located in posterosuperior segments (7, 6/7, 7/8, 8) was performed by the trainees with guidance and intermittent intervention of a senior surgeon. Data as: (1) percentage of time that the senior surgeon takes the surgery as main surgeon, (2) need for the senior surgeon to finish the procedure, (3) necessity of conversion, (4) bleeding with hemodynamic instability, (5) need for transfusion, (6) oncological surgical margins, were evaluated. Results: In total, 12 cases of complex laparoscopic liver resections were performed by the trainee. All cases included deep lesions situated on liver segments 7 or 8. The senior surgeon intervention occurred in a mean of 20% of the total surgical time (range, 0% to 50%). A senior intervention >20% was necessary in 2 cases. There was no need for conversion or reoperation. Neither major bleeding nor complications resulted from the teaching program. All surgical margins were clear. Conclusions: This preliminary report shows that hand-assistance is a safe way to teach complex liver resections without compromising patient safety or oncological results. More cases are still necessary to draw definitive conclusions about this teaching method.